Efektivitas Media Daring Google Classroom Dalam Pembelajaran Aqidah Akhlak Di MTAS At-Taqwa Tangerang - Dewi Intan; Iva Inayatul Ilahiyah (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2022)
Covid-19 that hit all corners of the world during 2020 caused various kinds of problems, one of them was problem of learning. Students cannot do learning at school or meet directly with teachers and learning does not work effectively because learning is done out of habit. Therefore, the MTs At-Taqwa Belendung Tangerang has a program that can solve learning problems during a pandemic that is Using Online Media Google Classroom . In line with this, this research focuses on 3 aspects: (1) How is the effectiveness of Using Online Media Google Classroom learning Aqidah Akhlak, (2) How is the effectiveness of Using Online Media Google Classroom learning Aqidah Akhlak? To solve problems and find answers to these three problems, this study uses a qualitative approach with the type of case study research. Data collection techniques using observation, interviews, and communication studies. In terms of analyzing this data, the researcher took what was stated by Miles and Huberman, the data analysis procedure included data reduction, data presentation and drawing conclusions. Data validity test was conducted through data credibility and data dependability and data confirmability. The focuses of the results of this study, that is: there are subject teachers who supervise, second, there is a quota from the school, third, there is support from the school to support learning aqidah akhlak using online mediaGoogle Classroom,fourth, good and proper time management that has been arranged by the school. While the inhibiting factors are the lack of students understanding the material due to not reading completely, lack of interest in reading, signal difficulties or poor internet network.